2015
DOI: 10.1111/bjd.13613
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of burning mouth syndrome: a population-based study

Abstract: Background Burning mouth syndrome (BMS) is defined as symptoms of persistent burning in the mouth without objective findings accounting for the symptoms. Objectives To calculate the point prevalence of BMS in Olmsted County, Minnesota, on December 31, 2010. Methods The Rochester Epidemiology Project (REP) medical records linkage system was used to identify BMS cases diagnosed or potentially diagnosed before December 31, 2009. Inclusion criteria were subjective oral discomfort, normal oral examination, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 14 publications
5
57
0
11
Order By: Relevance
“…Regarding the anatomical region of burning sensation, 58.3% of the patients reported higher frequency in the apex of tongue, even though the literature shows that the most common complaint was bilateral in the tongue sides 9,10 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Regarding the anatomical region of burning sensation, 58.3% of the patients reported higher frequency in the apex of tongue, even though the literature shows that the most common complaint was bilateral in the tongue sides 9,10 .…”
Section: Discussionmentioning
confidence: 95%
“…The most affected anatomical regions are tongue, followed by palate, lower lip and jugal mucosa 8 . Complaints are normally bilateral but it may also occur unilaterally 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms are often present on the tongue, distributed bilaterally, and occasionally associated with xerostomia and dysgeusia [59]. BMS has repeatedly been shown to be common in women over the age of 50 [59][60][61][62]. The etiology is unknown, but several mechanisms have been proposed with hormonal, psychiatric, and neuropathic bases [63][64][65].…”
Section: Secondary Burning Mouth Syndromementioning
confidence: 99%
“…Ample research shows that prevalence of BMS varies considerably, between 0.7% and 15%, depending on the population investigated 5,[7][8][9][11][12][13][14] . For example, one study found age-adjusted prevalence rates of 18.8 and 3.7 cases in women and men, respectively in 100,000 people 15 , while another investigation discovered that BMS occurs in 1 in every 1,000 subjects, mainly in women over 50 years old 16 . Also, the evaluation of 3,243 medical records found that 0.99% of patients could have BMS 17 .…”
Section: Bms Epidemiologymentioning
confidence: 99%